2020
DOI: 10.3389/fphar.2020.00256
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Ameliorates Diabetic Cardiomyopathy Through Apelin/Sirt3 Signalling to Improve Mitochondrial Dysfunction

Abstract: Myocardial contractile dysfunction in diabetic cardiomyocytes is a significant promoter of heart failure. Herein, we investigated the effect of icariin, a flavonoid monomer isolated from Epimedium, on diabetic cardiomyopathy (DCM) and explored the mechanisms underlying its unique pharmacological cardioprotective functions. High glucose (HG) conditions were simulated in vitro using cardiomyocytes isolated from neonatal C57 mice, while DCM was stimulated in vivo in db/db mice. Mice and cardiomyocytes were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…The mitochondrial electron transport chain is the main source of ROS, and SIRT3 can enhance mitochondria's ROS coping capacity by multiple factors 26 . Recent studies indicated that the protective effect of Apelin/APJ system may depend on SIRT3 and its downstream factors 27‐29 . A research showed that overexpression of Apelin significantly attenuated high glucose‐induced ROS and improved the expression of SIRT3, while Apelin's protection against high glucose‐induced ROS formation was diminished when SIRT3 was knocked out 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mitochondrial electron transport chain is the main source of ROS, and SIRT3 can enhance mitochondria's ROS coping capacity by multiple factors 26 . Recent studies indicated that the protective effect of Apelin/APJ system may depend on SIRT3 and its downstream factors 27‐29 . A research showed that overexpression of Apelin significantly attenuated high glucose‐induced ROS and improved the expression of SIRT3, while Apelin's protection against high glucose‐induced ROS formation was diminished when SIRT3 was knocked out 19 .…”
Section: Discussionmentioning
confidence: 99%
“…26 Recent studies indicated that the protective effect of Apelin/APJ system may depend on SIRT3 and its downstream factors. [27][28][29] A research showed that overexpression of Apelin significantly attenuated high glucose-induced ROS and improved the expression of SIRT3, while Apelin's protection against high glucose-induced ROS formation was diminished when SIRT3 was knocked out. 19 Hou et al also demonstrated that SIRT3 is essential for Apelin-induced angiogenesis in post-myocardial infarction of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a major component of Epimedium, Icariin attenuated myocardial infarct size and cell apoptosis by activating the PI3K/Akt/eNOS-dependent signal pathways [21]. In addition, Icariin ameliorated diabetic cardiomyopathy by preventing mitochondrial dysfunction through the Apelin/Sirt3 pathway [22]. Notopterygii Rhizoma et Radix has been widely used in clinical prescriptions to disperse cold and eliminate dampness in China.…”
Section: Discussionmentioning
confidence: 99%
“…The cardioprotective properties of icariin and its potential involvement in the modulation of the PI3K/Akt signaling pathway were also observed in different animal models of ischemia-reperfusion injury and cardiomyopathies. Indeed, icariin perfusion before ischemia induction and throughout reperfusion, ameliorates cardiac function improving left ventricular diastolic pressure, coronary flow and reducing infarct size, oxidative stress and cardiomyocyte apoptosis [ 178 , 185 , 186 , 187 ]. Moreover, icariin preserves the injured heart from pathological cardiac remodeling, characterized by hypertrophy and degeneration of CMs and inflammatory infiltration, down-regulating Matrix Metallopeptidases (MMP)-2 and MMP-9, increasing Bcl2 levels and decreasing Bax and caspase 3 [ 187 ].…”
Section: Plant Extracts and Their Role In Nutraceutical Supplementmentioning
confidence: 99%